2004
DOI: 10.1111/j.1464-410x.2003.04657.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing prostatic adenocarcinomas in men with a serum prostate specific antigen level of <4.0 ng/mL

Abstract: grading, and for the presence of PSA production. Tumours were classified as 'clinically insignificant' if the tumour volume was <0.5 mL and the Gleason score <7. RESULTSThe mean ( SD , range) preoperative PSA level was 3.04 (0.85, 0.8-3.8) ng/mL. Indications for biopsy included an abnormal digital rectal examination (61%), a PSA velocity of >0.75 ng/mL/year (12%), a strong family history of prostate cancer (3%), obstructive urinary symptoms (2%), or no obvious indication (23%). Thirty-eight (48%) tumours were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
1
25
0
2
Order By: Relevance
“…We attributed this mainly to the low tumor volume and low Gleason score of incidentally detected PCa because in most cases of PCa, serum PSA levels correlate well with tumor volume and Gleason score [26,27]. Similar to the results in the United States and western Europe, the diagnosed incidental PCa cases were primarily localized and well differentiated in our study [22,28].…”
Section: Mainlan Chinasupporting
confidence: 76%
“…We attributed this mainly to the low tumor volume and low Gleason score of incidentally detected PCa because in most cases of PCa, serum PSA levels correlate well with tumor volume and Gleason score [26,27]. Similar to the results in the United States and western Europe, the diagnosed incidental PCa cases were primarily localized and well differentiated in our study [22,28].…”
Section: Mainlan Chinasupporting
confidence: 76%
“…58 Experience with screening both in Chicago and Tyrol, Austria have reported similarly high rates of clinically significant tumors among men with a low PSA level. 59,60 Notably, in 1 series of 82 patients treated for metastatic disease, 4 patients had PSA levels Յ 2.0 ng/mL. 61 Finally, in our recent report from Southwest Oncology Group Study 8894, we noted that 153 of 1238 men with metastatic disease enrolled in this Phase III clinical trial had a PSA level Ͻ 20 ng/mL at the time of diagnosis.…”
Section: Prostate Carcinoma Screening In Men With Low Psa Levelsmentioning
confidence: 90%
“…35 We examined 5587 men in the placebo group, all of whom eventually underwent prostate biopsy. 36 We found that, for cancer detection, the area under the receiver-operating characteristic curve (a measure of the performance of a test; the area under the receiver-operating characteristic curve of the toss of a coin has a value of 0.5, whereas that for any test with 100% sensitivity at all specificities has an area of 1.0) for PSA screening was 0.68 (95% confidence interval [CI] 0.67-0.69), a reasonable level of test performance.…”
Section: -31mentioning
confidence: 99%